A community study on awareness of iron deficiency and screening early adolescents who are likely to be iron deficient in government schools - Reddy, Mohana I.; Parameshwara, Apoorva; Kumar, Kishore; Maski, Rahul; Nekkanti, Vineela; Ranganathan, Srinivasan (International Journal Of Community Medicine And Public Health, 2021)
Background: Iron deficiency is one of the major concerns of nutritional deficiencies in developing countries. Iron is an essential element for various biological processes. ID can result from inadequate intake or absorption of dietary iron, increased need during growth period of children and blood loss from infection. According to WHO, the prevalence of iron deficiency anaemia is 20% or higher. IDA in children has been linked to increased childhood morbidity and impaired cognitive development and school performance. Methods: A descriptive study was carried out on 413 government school children in Bangalore of age group of 11-16 years. Questionnaires were provided to assess their knowledge. The demographic details of the study subjects like height, weight and physical examination, dietary intake of foods by the children were collected. Results: The paired two sample t-test was used to calculate the significance between the pre and post-educational test. The measure of the subjective data of the parameters as BMI, physical examination, dietary history; indicates that out of 413 students who had undergone assessment for iron deficiency, 70.70% students might be healthy, 14.29%, 10.73% and 4.28% students might be mild, moderate and severely prone to ID respectively. Conclusions: This study provided students with knowledge of ID and awareness of signs and symptoms for early detection of ID.